Pengaruh Eksistensi Bandara International Lombok Terhadap Perkembangan Permukiman di PKW Perkotaan Praya - Haryono, Yuswan (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Inequality development causes delays for Praya development. MP3EI, changed conditions of Urban Praya through the construction of Lombok International Airport (BIL) that is represented as Regional Activity Center. The development began to grow including the settlements sector. The purpose of this study is to assess the effect of the presence of BIL on the development of settlements in Praya urban with quantitative descriptive method; through the identification residential development from the aspects existence of BIL, pattern and shape of its range, physical and non-physical variables that affect and changes pattern and Structures space. The results showed, the development of urban settlements do not occurs due to the direct presence of BIL but influenced by the roads and utility networks. Praya urban image map in 2006 and 2012 showing the development of settlement that is shaped